Технічні засоби для одночасного завантаження та розділення зернового вороху за розмірами - Мороз, С. М.; Васильковський, О. М.; Анісімов, О. В.; Moroz, Sergey; Vasylkovskii, Aleksey; Anisimov, Aleksandr (КНТУ, 2014)
В статті проведено аналіз конструкцій робочих органів сільськогосподарських машин для одночасного транспортування та решітного очищення зернового вороху від крупних домішок. Проведений аналіз дозволив встановити їх основні переваги та недоліки і запропонувати оригінальну конструкцію нового транспортера-сепаратора зерна. The aim of the article is to determine the most efficient working body for loading and separation of the grain size at the same time. The article is review and analysis of modern facilities for transporting and separating the grain size simultaneously. Exposed advantages and disadvantages of existing structures. A new original conveyor-separator that provides cleaning of grain from large impurities. Application of the new conveyor-separator will reduce grain damage during loading and improve further purification.
Technical means for simultaneous loading and separation of the grain heap size
Keywords: транспортер; сепаратор; розділення за розмірами; решітна поверхня; решето; зерновий ворох; зерно; conveyor; separator; separation by size; grate surface; sieve; grain heap; grain